SHIPPING AS A MANIFESTATION OF CULTURE: AN EXPLORATION OF VALUES, TRADITIONS, AND CULTURAL PRACTICES IN INDONESIA - David, Muhammad David; Adi, Panggih Nur (LPPM Universitas Labuhanbatu, 2025)
Cruise has become an integral part of civilization humans, especially in Indonesia which is an archipelagic country. Activities This No only functioning as means transportation and trade, but also reflects values culture, tradition and identity public maritime. However, modernization and globalization has bring challenge significant to preservation culture maritime, where many practice traditional start eroded by technology and change social. Research This aiming For document and analyze sustainability tradition maritime in modern context, with focus on values interwoven cultures in practice shipping. The methodology used in study This is method descriptive, which allows researcher For describe in a way systematic and accurate characteristics culture maritime. Through approach multidisciplinary that combines anthropology, history, and economics, research This exploring rituals, language, art, and role generation young in preservation values maritime. Research results show that although modern technology has change method cruise done, many community Still maintain traditional techniques and rituals. Departure rituals and ceremonies I'm grateful become part important from practice voyage, reflect spiritual relationship between humans and the sea. Besides that, research This find that integration technology with knowledge traditional, conservation culture through documentation and education, as well as development ecotourism maritime, is an important strategy in guard sustainability culture maritime. Policy government that supports protection rights public maritime also plays a role crucial in preservation tradition. With Thus, research This expected can give contribution academic and practical in effort preservation culture maritime, ensuring that inheritance culture This still alive and relevant in the modern era.